Virtual Reality Medical Training for COVID-19 Swab Testing and Proper Handling of Personal Protective Equipment: Development and Usability - Zikas, Paul; Kateros, Steve; Lydatakis, Nick; Kentros, Mike; Geronikolakis, Efstratios; Kamarianakis, Manos; Evangelou, Giannis; Kartsonaki, Ioanna; Apostolou, Achilles; Birrenbach, Tanja; Exadaktylos, Aristomenis K.; Sauter, Thomas C.; et al. (Frontiers in Virtual Reality, 2022)
Efficient and riskless training of healthcare professionals is imperative as the battle against the Covid-19 pandemic still rages. Recent advances in the field of Virtual Reality (VR), both in software and hardware level, unlocked the true potential of VR medical education (Hooper et al., The Journal of Arthroplasty, 2019, 34 (10), 2,278–2,283; Almarzooq et al., Virtual learning during the COVID-19 pandemic: a disruptive technology in graduate medical education, 2020; Wayne et al., Medical education in the time of COVID-19, 2020; Birrenbach et al., JMIR Serious Games, 2021, 9 (4), e29586). The main objective of this work is to describe the algorithms, models and architecture of a medical virtual reality simulation aiming to train medical personnel and volunteers in properly performing Covid-19 swab testing and using protective measures, based on a world-standard hygiene protocol. The learning procedure is carried out in a novel and gamified way that facilitates skill transfer from virtual to real world, with performance that matches and even exceeds traditional methods, as shown in detail in (Birrenbach et al., JMIR Serious Games, 2021, 9 (4), e29586). In this work we are providing all computational science methods, models together with the necessary algorithms and architecture to realize this ambitions and complex task verified via an in-depth usability study with year 3–6 medical school students.